How Stress Affects Your Budget—Stress Impacts on Starch Metabolism - Ribeiro, Camila; Stitt, Mark; Hotta, Carlos Takeshi (Frontiers in Plant Science, 2022)
Starch is a polysaccharide that is stored to be used in different timescales. Transitory starch is used during nighttime when photosynthesis is unavailable. Long-term starch is stored to support vegetative or reproductive growth, reproduction, or stress responses. Starch is not just a reserve of energy for most plants but also has many other roles, such as promoting rapid stomatal opening, making osmoprotectants, cryoprotectants, scavengers of free radicals and signals, and reverting embolised vessels. Biotic and abiotic stress vary according to their nature, strength, duration, developmental stage of the plant, time of the day, and how gradually they develop. The impact of stress on starch metabolism depends on many factors: how the stress impacts the rate of photosynthesis, the affected organs, how the stress impacts carbon allocation, and the energy requirements involved in response to stress. Under abiotic stresses, starch degradation is usually activated, but starch accumulation may also be observed when growth is inhibited more than photosynthesis. Under biotic stresses, starch is usually accumulated, but the molecular mechanisms involved are largely unknown. In this mini-review, we explore what has been learned about starch metabolism and plant stress responses and discuss the current obstacles to fully understanding their interactions.